The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2174/1871525717666190402121958
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones and the Risk of Aortic Aneurysm or Aortic Dissection: A Systematic Review and Meta-Analysis

Abstract: Objective: We performed a systematic review and meta-analysis to explore the risk of an aortic aneurysm or aortic dissection following fluoroquinolone administration. Methods: PubMed, Cochrane library, ClinicalTrials.gov, Embase and Google Scholar were systematically reviewed for controlled studies including adult patients exposed to fluoroquinolones with a primary outcome of aortic aneurysm or aortic dissection. Results: The meta-analysis was conducted by pooling the effect estimates of four controlled ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…Four meta-analyses on this issue have been published, and we have summarized the details in Table 3. [2,7,23,24] Though the major result of our meta-analysis was consistent with that of these former meta-analyses, differences and new findings between our meta-analysis and the former studies should be noted. First, these meta-analyses included no more than five studies.…”
Section: Comparison With Other Meta-analysessupporting
confidence: 87%
See 1 more Smart Citation
“…Four meta-analyses on this issue have been published, and we have summarized the details in Table 3. [2,7,23,24] Though the major result of our meta-analysis was consistent with that of these former meta-analyses, differences and new findings between our meta-analysis and the former studies should be noted. First, these meta-analyses included no more than five studies.…”
Section: Comparison With Other Meta-analysessupporting
confidence: 87%
“…Therefore, our metaanalysis is the most up-to-date and the broadest analysis; our analysis consolidates the results of the former meta-analyses. Second, we found that three of these meta-analyses used the HR of aortic aneurysm to replace the HR of aortic diseases; [7,23,24] this may underestimate the risk of occurrence of aortic diseases. We excluded this study, [19] when pooling the ORs.…”
Section: Comparison With Other Meta-analysesmentioning
confidence: 98%
“…Therefore, we suggest that the result was robust. Moreover, we reevaluated the NNH for aortic aneurysm or dissection because we also found that the study by Lee et al [18] had a more statistically significant RR than the pooled results in the two previous meta-analyses [7,24]. Finally, after adjusting the data, we revaluated the quality of the evidence for the primary outcome to help medical care providers make clinical decisions.…”
Section: Comparison With Other Meta-analysesmentioning
confidence: 97%
“…Therefore, our meta-analysis is the most up-to-date and the broadest analysis; our analysis consolidates the results of the former meta-analyses. Second, we found that three of these meta-analyses used the HR of aortic aneurysm to replace the HR of aortic diseases [7,23,24]; this may underestimate the risk of occurrence of aortic diseases. We excluded this study, [19] when pooling the ORs.…”
Section: Comparison With Other Meta-analysesmentioning
confidence: 98%
“…So our meta-analysis was the up-to-date and the broadest one and can consolidate the results of former meta-analyses. Secondly, we found that three of these meta-analyses used the HR of aortic aneurysm replaced the HR of aortic diseases; [7,22,23] it may reduce the risk of occurrence of aortic diseases. We excluded this study, [18] when combing with the OR together.…”
Section: Comparison With Other Meta-analysesmentioning
confidence: 98%